2013
DOI: 10.1002/jemt.22232
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic development of endoderm in chicken (Gallus gallus domesticus)

Abstract: The poultry industry is a sector of agribusiness which represents an important role in the country's agricultural exports. Therefore, the study about embryogenesis of the domestic chicken (Gallus gallus domesticus) has a great economic importance. The aim of this study was to evaluate embryonic development of the endoderm in chicken (Gallus gallus domesticus). Forty fertilized eggs of domestic chickens, starting from the 1st day of gestation and so on until the 19 days of the incubation were collected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
(16 reference statements)
2
9
0
Order By: Relevance
“…Corroborating this study, Alcântara et al (2013) identified in chicken embryos at 10 days of incubation, a shell with a typical respiratory epithelium, which was characteristic of rhea foetuses in the middle turbinate region at a proportionately later stage. The rostral nasal turbinate structure in 30-day rhea foetuses exhibited characteristics similar to those observed in the domestic chicken Gallus gallus (Kang et al 2013) at one year of age, and this species displayed stratified squamous epithelium.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Corroborating this study, Alcântara et al (2013) identified in chicken embryos at 10 days of incubation, a shell with a typical respiratory epithelium, which was characteristic of rhea foetuses in the middle turbinate region at a proportionately later stage. The rostral nasal turbinate structure in 30-day rhea foetuses exhibited characteristics similar to those observed in the domestic chicken Gallus gallus (Kang et al 2013) at one year of age, and this species displayed stratified squamous epithelium.…”
Section: Discussionsupporting
confidence: 71%
“…According to Daniely et al (2004), stem cells are capable of differentiating into cells and mucussecreting hair during normal morphogenesis of the tracheal epithelium. In this study, the identification of hair cells occurred in the late period, considering the incubation time of rheas relative to that observed in domestic hens, with pseudostratified epithelium with ciliated cells being reported in this species at six days (Alcântara et al 2013). In contrast, Kalnins & Porter (1969) observed in this same species, tracheal epithelium presenting cells with single primary cilium at 15 days of age.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations